Tumor-intrinsic YTHDF1 drives immune evasion and resistance to immune checkpoint inhibitors via promoting MHC-I degradation - Wanzun Lin; Li Chen; Haojiong Zhang; Xianxin Qiu; Qingting Huang; Fangzhu Wan; Ziyu Le; Shikai Geng; Anlan Zhang; Sufang Qiu; Long Chen; Lin Kong; et al. (Nature Communications, 2023)
YTHDF1 is an m6A reader that binds to methylated RNA and facilitates translation. Here the authors show that tumor intrinsic YTHDF1 promotes tumorigenesis by regulating lysosomal proteolysis of MHC-I and that YTHDF1 targeting boosts anti-tumor immunity and response to immunotherapy in preclinical cancer models.